2018
DOI: 10.18632/oncotarget.24762
|View full text |Cite
|
Sign up to set email alerts
|

Physical training interventions for children and teenagers affected by acute lymphoblastic leukemia and related treatment impairments

Abstract: A decreased physical fitness has been reported in patients and survivors of acute lymphoblastic leukemia (ALL). This is influenced by the negative effects of the disease and by the treatments of childhood cancer.In the past, children were advised to recover in bed, and to take as much relax as possible. Nowadays, it is considered that too much immobility may result in a further decrease of physical fitness and functioning. Exercise training for ALL children has frequently been reported to improve physical fitn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 98 publications
0
14
0
7
Order By: Relevance
“…www.e-apem.org intervention effect on total body BMD. 72) Intrahospital supervised exercise may also considerably improve children's quality of life (QoL) and overall health status during treatment periods. 73)…”
Section: Management and Recommendationsmentioning
confidence: 99%
“…www.e-apem.org intervention effect on total body BMD. 72) Intrahospital supervised exercise may also considerably improve children's quality of life (QoL) and overall health status during treatment periods. 73)…”
Section: Management and Recommendationsmentioning
confidence: 99%
“…It was conducted among children after cancer treatment who did not participate in supervised rehabilitation programs. Most studies in this domain usually assess the impact of particular rehabilitation programs and activities on physical fitness and quality of life [18,19,20,36,37]. However, our study shows the functional status of children who were not involved in the rehabilitation process despite severe treatment.…”
Section: Discussionmentioning
confidence: 69%
“…As a result, it is crucial to implement early rehabilitation and encourage young patients to undertake physical activity by providing them with access to physical activities focused on the interests of a given age group depending on sex. Simioni et al [20] showed that properly selected physical activity in pediatric patients during and after cancer treatment results in a number of favorable changes. It positively influences musculoskeletal and neuromuscular systems, improves cardiovascular and respiratory parameters, increasing physical capacity and reducing metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALL patients also are at a higher risk of developing metabolic syndrome, which again is amplified by physical inactivity both during and after therapy. Recently, several physical training intervention protocols have become available for children with ALL, and promising results regarding both obesity and metabolic alterations are being published [26]. Hence, nutritional counseling should be provided and physical activity promoted both during and after the cessation of ALL treatment in order to decrease subsequent long-term health risks.…”
Section: Discussionmentioning
confidence: 99%